Teacher Use of School Connectedness Strategies With Underrepresented Youth in a Low-Income Middle School - Deborah E. Tyndall; Mitzi C. Pestaner; Shannon B. Powell; Travis E. Lewis; Carlos R. Melendez (The University of Alabama, 2022)
Adolescents in low-income and rural communities are at a higher risk for mental health concerns. This study used a mixed-methods, community-based participatory research design to examine teachers' experiences managing students with emotional and mental health needs in a low-income middle school serving underrepresented youth. Barriers to connecting positively with students included disruptive student behaviors, a lack of student interest, and an emphasis on accountability measures for academic achievement. Three themes emerged: (a) disruptive student behavior resulted in a whack-a-mole approach to managing emotional health needs; (b) learning was often put on the back burner as teachers attempted Maslow before Bloom; and (c) a lack of training and limited time to connect positively with students contributed to missed connections. Findings from this study indicate that additional resources and staff training are needed to help rural, low-income schools support students who have emotional and mental health needs.